Hubungan pendidikan karakter remaja terhadap prestasi belajar : pendidikan karakter remaja dan prestasi belajar - Nike Ardila Ardila (Yayasan Pendidikan Medika Indonesia, 2022)
Abstract Adolescent is a transition period from childhood to adulthood. Morality development task of adolescent can be tought by using character education in the school. The factors that influence learning achievement are undisciplined in making a task and lower curiosity. The aim of this research is to know the correlation of adolescents’ character education to learning achievement at senior high school 8 pekanbaru that was designed by using descrptive correlation of research and cross sectional approach. The sampel of this research was 280 respondent that were taken by inclusion criteria using stratified random sampling technique. The measuring instruments used are questionnaire and observation. The analysis is used was univariate analysis to determine the frequency distibution and bivariate analysis using chi-square test. The results showed that from 129 respondent that need consideration (B score) of character education, 2 respondent had been categorized into very good learning achievement (0,7%), 7 respondent had been categorized into good learning achievement (2,5%) dan 120 respondent had been categorized into pretty good learning achievement (42,9%). From 151 respondent that had good character education (score A). 110 respondent had been categorized into very good learning achievement (39,3%), 38 respondent had been categorized into good learning achievement (13,6%), and 3 respondent had been categorized into pretty good learning achievement (1,1%). Related to chi-square test result showed that p-value (0,000) < alpha (0,05), means that there is a significant correlation between adolescents’ character education and learning achievement. Be suggestions to family, teacher, and parent for improving adolescents’ character in repairing learning achievement.